KAJIAN PUSTAKA PENINGKATAN KELARUTAN NAPROKSEN MELALUI PEMBUATAN KOKRISTAL DENGAN SCREENING KOFORMER SECARA IN SILICO - Giovanni
Naproxen is a non-steroidal anti-inflammatory drug (NSAID) which is generally used to reduce pain, fever, swelling, or stiffness caused by arthritis and dysmenorrhea. Based on Biopharmaceutical Classification System (BCS), naproxen is classified as Class II drug with aqueous solubility of 15.9 mg/L at 25?C. The bioavailability of BCS Class II drugs is limited by their solubility. Cocrystal formation is one of few methods to increase solubility of drugs. Hence in this study, we aim to increase the solubility of naproxen by cocrystal formation. Coformer selection is one of the most important steps in cocrystal formation. In this study, coformer selection is conducted via in silico screening using Cambridge Structural Database (CSD). Naproxen and a set of prospective coformers will go through two stage screening procedure i.e. molecular complementarity and hydrogen bonding propensity. Based on this screening process and literature review, resorcinol is a potential coformer for naproxen to form higher solubility cocrystals. This screening result can be used as a guidance for experimental cocrystal screening.